AN ANALYSIS ACTIVE VOICE AND PASSIVE VOICE USED ON INSTAGRAM CAPTIONS WRITTEN BY K-POPERS - Triana, Devi; Simorangkir, Tessaria; Sidabalok, Anzelly Hernita (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2024)
This study aimed to analyze active voice and passive voice used on Instagram captions written by K-Popers. The existence of social media has become common communication among K-Popers national and internasional boundries. Instagram is the most social media platform as a mobile application for sharing photos, video and stories. K-Popers usually upload their idols' photos ot videos on Instagram, and they usually use English as their caption put on their post. Through the English captions on Instagram, active voice and passive voice appears in their English. This study used library research design. The writers chose the accounts from hastag #Kpop. The writers had figured out the data which were posted on Januari to July 2024 from two K-Popers which have been choosen in the form of sentences on Instagram captions. Two K-Popers in different accounts which have been choosen by writers, they are @sunghoonsfav and @syaquilla.1. The writers analyzed 20 Captions from two K-Popers accounts. Based on the analysis result by screenshot the K-Popers post with #Kpop, Active voice in the form of simple present tense was the most appears in this study, especially on Instagram accounts of @sunghoonsfav and @syaquilla.1. It appears 13 times from both K-Popers account. It can be concluded that Active voice in form of simple present tense was the most common appear used on Instagram captions written by K-Popers.